2016
DOI: 10.1007/s10514-016-9583-z
|View full text |Cite
|
Sign up to set email alerts
|

Head stabilization in a humanoid robot: models and implementations

Abstract: Neuroscientific studies show that humans tend to stabilize their head orientation, while accomplishing a locomotor task. This is beneficial to image stabilization and in general to keep a reference frame for the body. In robotics, too, head stabilization during robot walking provides advantages in robot vision and gaze-guided locomotion. In order to obtain the head movement behaviors found in human walk, it is necessary and sufficient to be able to control the orientation (roll, pitch and yaw) of the head in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 37 publications
1
12
0
Order By: Relevance
“…In terms of application to robotics, the stabilization was effective even with simplified linear control, and results in dramatically improved verticality estimation. Locating IMU in a robot's head and implementing the head stabilization strategy has been recently demonstrated in several humanoid robots applications with a view to mimic human gaze stabilization behavior [22]; to improve gaze stabilization for visual tracking [23], and to efficiently coordinate the robot's body movement [23,24]. Whereas some progress has been achieved in transferring anthropomorphic behaviors to humanoid robots, substantial research and development challenges remain in particular the role of head stabilization in resolution of gravitoinertial ambiguity.…”
Section: Discussionmentioning
confidence: 99%
“…In terms of application to robotics, the stabilization was effective even with simplified linear control, and results in dramatically improved verticality estimation. Locating IMU in a robot's head and implementing the head stabilization strategy has been recently demonstrated in several humanoid robots applications with a view to mimic human gaze stabilization behavior [22]; to improve gaze stabilization for visual tracking [23], and to efficiently coordinate the robot's body movement [23,24]. Whereas some progress has been achieved in transferring anthropomorphic behaviors to humanoid robots, substantial research and development challenges remain in particular the role of head stabilization in resolution of gravitoinertial ambiguity.…”
Section: Discussionmentioning
confidence: 99%
“…• The subsystem Semicircular canals simulates the kinematic model explained in the previous section. The components of the angular acceleration vector resulting from this subsystem, either expressed in the system R0 (consideration of orthogonal semicircular canals) or in the system R3 (consideration of non-orthogonal semicircular canals), are integrated to obtain the angular velocity vector and subsequently each component of this vector is introduced into the transfer function (2). As a result, the volume of endolymph displaced by the cupula in the three semicircular canals (posterior, anterior and lateral) is obtained.…”
Section: Kinematic Model With Vestibular Systemmentioning
confidence: 99%
“…The design of a biologically-inspired artificial VS as a sensor for controlling robot heads during motion has received a great interest in robotics to regulate and stabilize gaze (see e.g. [2,10,3,5]). It has been demonstrated that the balance of robots that are not endowed with a vestibular sensor is clearly inferior that of humans [4].…”
Section: Introductionmentioning
confidence: 99%
“…The results are not optimal because we need to use a better controller with at least an integration of the errors in order to reduce static errors. There are many other ways to improve the control [7], [18] or see [8] for a review. Here, however, we focus on the hardware.…”
Section: Controllermentioning
confidence: 99%